Gastric Emptying, Incretin Hormone Secretion, and Postprandial Glycemia in Cystic Fibrosis—Effects of Pancreatic Enzyme Supplementation - Kuo, Paul; Stevens, Julie E.; Russo, Antonietta; Maddox, Anne; Wishart, Judith M.; Jones, Karen L.; Greville, Hugh; Hetzel, David; Chapman, Ian; Horowitz, Michael; Rayner, Christopher K. (The journal of clinical endocrinology and metabolism, 2011)
Context:Postprandial hyperglycemia is an important clinical problem in cystic fibrosis (CF), but the contribution of fat malabsorption, rapid gastric emptying, and the incretin axis has not been widely considered.Objective:The aim of this study was to evaluate these aspects of gut function in nondiabetic CF patients.Design and Setting:We conducted a randomized, double-blind, placebo-controlled crossover study at a clinical research laboratory.Patients:Five nondiabetic CF patients (three males; age, 25.8 ± 1.0 yr; body mass index, 20.2 ± 1.1 kg/m2) with exocrine pancreatic insufficiency and six healthy subjects of similar age and body mass index participated in the study.Interventions:CF patients consumed a radiolabeled mashed potato meal on 2 separate days, together with four capsules of Creon Forte (100,000 IU lipase) or placebo. Healthy subjects consumed the meal once, without pancreatic enzymes.Main Outcome Measures:Gastric emptying was measured using scintigraphy, and blood was sampled frequently for blood glucose and plasma glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP), and glucagon concentrations.Results:CF patients had more rapid gastric emptying (P < 0.001), impaired secretion of GLP-1 (P < 0.01) and GIP (P < 0.001), and greater postprandial glycemic excursions (P < 0.001) than healthy subjects. Pancreatic enzyme supplementation normalized gastric emptying and GLP-1 secretion and tended to increase glucagon (P = 0.08), but did not completely restore GIP secretion or normalize postprandial blood glucose. There was an excellent correlation between gastric emptying and blood glucose concentration at 60 min (R = 0.75; P = 0.01).Conclusions:Pancreatic enzyme supplementation plays an important role in incretin secretion, gastric emptying, and postprandial hyperglycemia in CF.